2017
DOI: 10.2217/fmb-2016-0211
|View full text |Cite
|
Sign up to set email alerts
|

Novel human Metapneumovirus with a 180-Nucleotide Duplication in the G Gene

Abstract: This study reported on the circulation of a novel HMPV with a 180-nucleotide duplication in the G gene, but no clinical changes in related cases were observed. Their prevalence increased during the last season suggesting changes in viral features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 16 publications
7
28
0
Order By: Relevance
“…Further detailed sequence analyses of HMPV strains have suggested two clades, A2a and A2b, in the A2 subgroup . Recently, unique A2b 180nt‐dup HMPV were detected in Japan and Spain . Our work has suggested that HMPV‐A2b 180nt‐dup emerged between 2011 and 2013 .…”
Section: Numbers Of Hmpv Strains Detected In Yokohama City Japan Betmentioning
confidence: 59%
See 2 more Smart Citations
“…Further detailed sequence analyses of HMPV strains have suggested two clades, A2a and A2b, in the A2 subgroup . Recently, unique A2b 180nt‐dup HMPV were detected in Japan and Spain . Our work has suggested that HMPV‐A2b 180nt‐dup emerged between 2011 and 2013 .…”
Section: Numbers Of Hmpv Strains Detected In Yokohama City Japan Betmentioning
confidence: 59%
“…In 2017, three novel HMPV A2b strains with 111nt‐dup in the G gene (A2b 111nt‐dup HMPV) were identified by the present team. Before 2016, no A2b 111nt‐dup HMPV strain had been detected (Table ). Relevant basic and clinical characteristics of the three individuals infected with A2b 111nt‐dup HMPV are summarized in Table .…”
Section: Numbers Of Hmpv Strains Detected In Yokohama City Japan Betmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed phylogenetic analysis of HMPV strains shows two distinct lineages, A2a and A2b, in the subgroup A2 (7). Recently, unique variant HMPV strains possessing a 180-or 111-nucleotide duplication (nt-dup) in the G gene were detected in Japan, Spain, Vietnam, and China (GeneBank accession number MF462419.1) (8)(9)(10). These variants belong to the subgroup A2b and are called HMPV A2b180nt-dup and HMPV A2b111nt-dup, respectively (8,10).…”
Section: Short Communicationmentioning
confidence: 99%
“…A1 and A2a were the least commonly detected subgroups globally and this could probably explain why they were not detected in Kilifi. In contrast to continued circulation of clade A2b (18), in Kilifi, A2b circulated from 2007 to November 2012 and no longer. Occurrence of the clade A2c (41) has increased in Kilifi in recent years, as similarly reported in Bangladesh and Croatia (15,16), suggestive of global spread of HMPV variants.…”
Section: Discussionmentioning
confidence: 93%